Evaluation of antimicrobial activity and bronchodialator effect of a polyherbal drug-Shrishadi - Kajaria, Divya Kumari; Gangwar, Mayank; Kumar, Dharmendra; Sharma, Amit Kumar; Tilak, Ragini; Nath, Gopal; Tripathi, Yamini Bhusan; Tripathi, JS; Tiwari, SK (Asian Pacific journal of tropical biomedicine, 2012)
Objective:To investigate antimicrobial and bronchodialator effect of hydroalcholic extract of polyherbal drug Shirishadi containing Shirisha(Albezzia lebbeck),Nagarmotha(Cyprus ratandus) & Kantakari(Solanum xanthocarpum).Methods:Antimicrobial activity was evaluated by discdiffusion method and MIC,MBC,MFC were calculated by micro dilution method.Hydroalcholic extract of this preparation was investigated for its phytochemical analysis,phenol and Oavonoid were determined by speclrophotometric method and in vivo bronchodilator effect was analysed by convulsion time.Results:The phytochemical tests revealed presence of alkaloids, anthraquinones,carbohydrates,flavonoids,saponins and tannins.The antimicrobial result showed the MIC of 6.25 mg/ml.against Staphylococcus aureus and 12.5 mg/mL.for Escherichia coli and 12.5 mg/mL against remaining bacteria tested,with strong antifungal activity.The maximum inhibition zone is found against Pseudomonas aeruginosa with MIC 16 mg/mL Drug showed significant bronchodilator effect with 27.86%& 36.13%increase in preconvulsion time of guinea pigs prebeated with 100 & 200 mg/kg body weight of extract.Conclusions:The study reveals that the extracts possess antibacterial activity and antifungal activity in a dose dependent manner. This antimicrobial property may be due to presence of several saponins,further studies are highly needed for the drug development.